The Asian Infrastructure Investment Bank (AIIB) Loan Projects: Analyzing The People’s Republic of China’s Multilayered Multilateralism Strategy to Turkey (2016-2018) - Anggara Raharyo; Shelia Saady (President University, 2020)
The establishment of Asian Infrastructure Investment Bank (AIIB) was first marked with the proposition made by People’s Republic of China (PRC) President Xi Jinping in 2013. Many since then believes that the establishment of the AIIB is part of PRC’s bigger plan that is the Belt and Road Initiatives (BRI). The significance of Turkey strategic position for the implementation of BRI, it is very crucial for PRC to maintain a steady flow of cooperation with Turkey. Out of 93 members that has joined as a part of AIIB, Turkey stands as the second largest loan receiver by the end of 2018. This article argues that PRC has been using AIIB as part as their BRI plan through its multilayered-multilateralism strategy to Turkey. This article analyze the loan policies that has been made by PRC and AIIB to Turkey from 2016 to 2018